THE EFFECT OF FINANCIAL LEVERAGE ON FINANCIAL INSTABILITY: A STUDY OF A SAMPLE OF COMPANIES LISTED ON THE IRAQ STOCK EXCHANGE - Israa Muneer Obaid; Karrar samawi (Scholars Digest Publishing, 2025)
This research examines the impact of financial leverage on financial instability in a sample of companies listed on the Iraq Stock Exchange, specifically focusing on Baghdad Soft Drinks Company from 2019 to 2023. Financial leverage, the use of debt to amplify shareholder returns, can lead to increased risks, especially when mismanaged or excessively relied upon. This study investigates the relationship between debt ratios and financial stability indicators, aiming to identify strategies that balance the benefits of leverage with the risks it entails. The research hypothesizes that a higher financial leverage correlates with greater financial instability and increased risk of liquidity problems. Through an analysis of key financial ratios such as Debt-to-Equity, Debt-to-Assets, and Interest Coverage, the study tracks the company's financial health over the period. The findings reveal a gradual increase in debt levels, yet the company maintains relatively low debt ratios compared to industry standards, indicating stable financial management. This study highlights the importance of managing debt effectively to prevent financial distress while also leveraging financial tools for growth. The research offers practical recommendations for companies and policymakers to ensure sustainable financial practices and strengthen market stability, especially during times of economic uncertainty.
Keywords: Effect of Financial, Financial Instability.